2020
DOI: 10.1002/ajpa.24107
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of maternal lineages in hunter‐gatherer societies of the southern coast of Tierra del Fuego, Argentina

Abstract: Objectives: The aim of this work is to explore the maternal genetic diversity of hunter-gatherers of the southern Tierra del Fuego, specifically the north coast of Beagle Channel, the Península Mitre, and Isla de los Estados through ancient mitochondrial DNA analysis. Materials and Methods: The hypervariable regions 1 and 2 of the mitochondrial genome of five individuals from the north coast of Beagle Channel, six individuals from Península Mitre, and one individual from Isla de los Estados were analyzed. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…In addition to the work by Postillone et al (2020), D1g was found in many ancient Fuegian samples dated between <2000 ybp (de la Fuente et al, 2015), 200–132 ybp (Raghavan et al, 2015), 815–220 ybp (Nakatsuka et al, 2020), and 1504–818 ybp (Crespo et al, 2020). In northern continental Patagonia, D1g was found in four ancient samples, two of them dated 2300 ± 47 and 1225 ± 47 ybp, respectively (Crespo, Favier‐Dubois, et al, 2017; Favier‐Dubois, 2009; García‐Guraieb et al, 2015).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition to the work by Postillone et al (2020), D1g was found in many ancient Fuegian samples dated between <2000 ybp (de la Fuente et al, 2015), 200–132 ybp (Raghavan et al, 2015), 815–220 ybp (Nakatsuka et al, 2020), and 1504–818 ybp (Crespo et al, 2020). In northern continental Patagonia, D1g was found in four ancient samples, two of them dated 2300 ± 47 and 1225 ± 47 ybp, respectively (Crespo, Favier‐Dubois, et al, 2017; Favier‐Dubois, 2009; García‐Guraieb et al, 2015).…”
Section: Resultsmentioning
confidence: 75%
“…In addition, five C1b samples ascribed to the Haush and Yámana ethnic groups were dated to between 1975 ± 25 and 490 ± 25 14 C ybp (Nakatsuka et al, 2020). Samples from other studies performed in the region were ascribed to the C1 haplogroup (Crespo et al, 2020; de la Fuente et al, 2015; Moraga et al, 2010). Unfortunately, no specific resolution was reached due to methodological limitations, although, it is probable that some of these samples belong to the C1b haplogroup.…”
Section: Resultsmentioning
confidence: 99%
“…Four individuals (two from Plains and two from Sierras ) belonged to the sub‐haplogroup D1g (D1 +16187 ) with additional mutations at positions 16189 and 16209 (H9), which are diagnostic of lineage D1g5 (Bodner et al, 2012). D1g5 is mainly distributed in populations from Patagonia, both modern (de Saint Pierre et al, 2012; Gómez‐Carballa et al, 2016), and ancient (Arencibia et al, 2019; Crespo et al, 2017, 2020; Motti et al, 2019; Parolin et al, 2019). It was also found in modern populations of Western Argentina (García et al, 2018; Motti, 2012), Central Chile (Gómez‐Carballa et al, 2016), and in ancient samples from the Puna in Northwestern Argentina (Postillone et al, 2017) and from the Pampas region (Roca‐Rada et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…There is a growing body of research on the genetic profile of ancient American populations, which provides a temporal context for the study of the peopling of the continent (de la Fuente et al, 2015;Lindo et al, 2018;Llamas et al, 2016;Moraga et al, 2010;Moreno-Mayar et al, 2018;Nakatsuka, Lazaridis, et al, 2020;Posth et al, 2018). Besides, several aDNA studies of pre-Hispanic populations from Argentina have been published, covering most of the territory (Arencibia et al, 2019;Carnese et al, 2010;Crespo et al, 2016Crespo et al, , 2018Crespo et al, , 2020García et al, 2021;Mendisco et al, 2014;Motti et al, 2015;Nakatsuka, Luisi, et al, 2020;Nores et al, , 2017Parolin et al, 2020;Postillone et al, 2017Postillone et al, , 2020Roca-Rada et al, 2021;Russo et al, 2017;Russo, Mendisco, et al, 2018;Tavella et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Estudios bioantropológicos basados en dimensiones corporales, craneométricas y modificaciones de la bóveda craneal, mostraron que todos los grupos cazadores-recolectores de Patagonia Austral están relacionados biológicamente, aunque existiría un vínculo más estrecho entre aquellos que habitaron Santa Cruz/Magallanes y el norte de Tierra del Fuego que entre estos y los que ocuparon el sur de la Isla y el archipiélago occidental (e.g., Cocilovo et al, 2019). Sin embargo, los resultados obtenidos desde la genética indican una mayor relación entre los grupos que habitaron ambas subregiones de Tierra del Fuego (Crespo et al, 2020;de la Fuente et al, 2015). De acuerdo con los resultados obtenidos en este trabajo, es posible que las poblaciones humanas de Tierra del Fuego tuvieran una predisposición similar a padecer RB por causas del desarrollo.…”
Section: Discussionunclassified